Hubungan Pola Asuh Orang Tua Terhadap Kecerdasan Linguistik Anak Kelompok A Di TK Aisyiyah Basin 3 Klaten Tahun Ajaran 2015/2016 - Puspitasari, Desi; , Ilham Sunaryo, M.Pd (2016)
The family is an institution of education is first and foremost, as the earliest give a lot of treatment to children. Parents have an important role as responsible in directing children and provide education in an effort to personal development of children. This study aims to determine the relationship between parents' parenting democratic towards linguistic intelligence A group of children in kindergarten Aisyiyah Basin 3 Klaten Academic Year 2015/2016. This study uses a uantitative descriptive design. The population in this study were 58 children and taken a sample of 34 children by sing Simple Random Sampling. Data were analyzed using Product Moment orrelations. Based on the analysis result that there is a relationship between parents' parenting democratic towards linguistic intelligence A group of children in kindergarten Aisyiyah Basin 3 Klaten Academic Year 2015/2016. This is evidenced by the results rxy amounted to 0,477, rt ts 1% amounted to 0,442, rt ts 5% amounted to 0,344 thus it can be concluded that rxy > rt 1% > rt ts 5% (0,447>0,442˃0,344) which shows Ho rejected, it means hat there is a positive correlation between democratic parenting style of the linguistic intelligence of children in group A in kindergarten Aisyiyah Basin 3 Klaten of the school year in 2015/2016